Prioritizing economic growth over environmental protection: A rhetorical situation of President Joko Widodo's speeches - Poerwaningtias, Intania (Jurnal Komunikasi, 2025)
This study analyzes presidential speeches that reflect state policies, the president's political direction, and tools for shaping public opinion regarding environmental issues. Using the corpus linguistic analysis method, this study examines 160 speeches by the President of the Republic of Indonesia, Joko Widodo, throughout 2019-2024 that use the keywords environment, climate change, climate crisis, and global warming. Using the rhetorical situation theory, this study finds that the president's speeches on the environment are driven by three main factors, namely new capital city development, economic growth efforts, and engagement in international forums. International audiences and economic actors also influence the themes of the speeches. Furthermore, the study finds that the president's speech rarely addresses environmental issues that are close and directly impact the public, does not highlight environmental justice issues, and resolves environmental problems. This study offers novelty in the analysis of the president's environmental speeches with corpus linguistic analysis, which is still rare.